Proceedings of the 7th International Workshop on Challenges of Large Applications in Distributed Environments 2009
DOI: 10.1145/1552315.1552317
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of service choreography for data-intensive computing

Abstract: As the number of services and the size of data involved in workflows increases, centralised orchestration techniques are reaching the limits of scalability. In the classic orchestration model, all data pass through a centralised engine, which results in unnecessary data transfer, wasted bandwidth and the engine to become a bottleneck to the execution of a workflow. Choreography techniques, although more complex to model offer a decentralised alternative and are the optimal architecture for data-centric workflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
12
0
6
Order By: Relevance
“…Different from orchestrations, choreographies don't have a single point of control or coordination [3]. Choreographies tend to be more efficient than orchestrations because the probability to have a bottleneck in the system is reduced [5].…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Different from orchestrations, choreographies don't have a single point of control or coordination [3]. Choreographies tend to be more efficient than orchestrations because the probability to have a bottleneck in the system is reduced [5].…”
Section: Basic Conceptsmentioning
confidence: 99%
“…The XLCC language was derived from LCC, which is a compact declarative language [5] deployed in the OpenKnowledge project for describing and executing WS choreography between peers. LCC choreography specifications are also executable, but until now LCC interpreters have only been produced for peer-to-peer and service architectures, not for a Web environment.…”
Section: Overview Of Xlccmentioning
confidence: 99%
“…The centralized service composition has advantages of simple topological structure and high maintainability, so it has been widely adopted in applications, such as Web Services Business Process Execution Language (BPEL)–based applications. However, in some cases, the centralized service composition may have heavy network traffic to make its mediator become a bottleneck . On the other hand, due to its features, the decentralized service composition can mitigate the issues of the centralized service composition.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, due to its features, the decentralized service composition can mitigate the issues of the centralized service composition. Decentralized service compositions have received growing attention, and a number of issues have been discussed, such as the decentralized system design, implementation, deployment, application, and analysis . It was shown that, if a decentralized composition is built and deployed properly, the composition can achieve better performance and reduce network traffic when compared with the corresponding centralized composition .…”
Section: Introductionmentioning
confidence: 99%